A simple and wavelength-flexible procedure for fabricating phase-shifted fibre Bragg gratings - Chehura, Edmon; James, Stephen W.; Tatam, Ralph P. (IOP Publishing, 2010)
A simple procedure for fabricating phase-shifted fibre Bragg gratings (PSFBGs) that does not require the use of a phase-shifted phase mask is presented. Two standard fibre Bragg gratings (FBGs) of equal length and with the same Bragg wavelength are inscribed sequentially in a single mode optical fibre, such that the FBGs overlap physically by one grating period. This procedure induces a spectral hole in the middle of the reflection spectrum, equivalent to a pi-phase-shifted FBG. PSFBGs have been fabricated in the 1300 nm and 1550 nm wavelength bandwidths, demonstrating flexibility in the choice of the centre wavelength. The PSFBGs fabricated are compared with a model based on a modified Rouard's method, which is subsequently used to investigate the influence of translation stage errors on the fabrication of the PSFBGs. The model demonstrates that the strength/reflectivity of the PSFBG influences the spectral-hole linewidth as well as the finesse of the device while the length of the PSFBG affects only the linewidth of the spectral hole but not the finesse of the device. The PSFBG devices produced by this technique are reproducible and the fabrication process is fast and is well suited for the fabrication of WDM PSFBGs.
Keywords: optical fibre Bragg gratings phase-shifted Bragg gratings Rouard's model scanning beam technique optical-fibers laser filter masks